Pharmacology and immuno-virologic efficacy of once-a-day HAART in African HIV-infected children: ANRS 12103 phase II trial - Boubacar Nacro; Emmanuelle Zoure; Hervé Hien; Hassane Tamboura; François Rouet; Adama Ouiminga; Ali Drabo; Souleymane Yameogo; Alain Hien; Hélène Peyriere; Olivier Mathieu; Deborah Hirt; et al. (The World Health Organization, 2011)
OBJECTIVE: To assess 12-month survival, pharmacokinetics, immunologic and virologic efficacy, tolerance, compliance and drug resistance in HIV-infected children in Bobo-Dioulasso, Burkina Faso, receiving once-daily highly-active antiretroviral therapy as a combination of didanosine (DDI), lamivudine (3TC) and efavirenz (EFV). METHODS: In the ANRS 12103 open phase II trial, HIV-infected children were examined at inclusion and monthly thereafter. CD4+ T-lymphocyte (CD4) count, plasma concentration of ribonucleic acid (RNA) of human immunodeficiency virus type 1 (HIV-1) and haematologic and biochemical parameters were measured at baseline and every trimester. HIV-1 resistance testing was performed in case of viral escape. Drug plasma concentrations were determined with high-performance liquid chromatography. FINDINGS: From February 2006 to November 2007, 51 children (39% girls) with a mean age of 6.8 years were enrolled and treated for 12 months. At baseline, Z scores for mean weight-for-age and mean height-for-age were -2.01 and -2.12, respectively. Mean CD4% was 9.0. Median plasma HIV-1 RNA viral load was 5.51 log10 copies per millilitre (cp/ml). Two children (3.9%) died and another 11 (22%) suffered 13 severe clinical events. At month 12, mean WAZ had improved by 0.63 (P < 0.001) and mean HAZ by 0.57 (P < 0.001). Mean CD4% had risen to 24 (P < 0.001). Viral load was below 300 RNA cp/ml in 81% of the children; HIV resistance mutations were detected in 11 (21.6%). CONCLUSION: The once-a-day combination of DDI + 3TC + EFV is an alternative first-line treatment for HIV-1-infected children. Dose adjustment should further improve efficacy.